The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1002/1097-0142(19870501)59:9<1661::aid-cncr2820590923>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Familial pancreatic adenocarcinoma in three generations. A case report and a review of the literature

Abstract: Although scattered case reports of familial clustering of pancreatic cancer have appeared in the literature, hereditary factors have not been clearly associated with increased risk for this malignancy. The current report documents the familial occurrence of pancreatic adenocarcinoma in three women of consecutive generations who died of their disease at progressively younger ages. The diagnoses are histologically confirmed in all three cases. Although two of the women carried a single known risk factor for panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 14 publications
0
24
0
1
Order By: Relevance
“…Familial aggregation of pancreas cancer has been reported in various populations [8][9][10][11] , including the families in this current study 12 . Familial clustering of pancreas or other cancers may be influenced by shared environmental factors and by shared genes.…”
Section: Introductionmentioning
confidence: 85%
“…Familial aggregation of pancreas cancer has been reported in various populations [8][9][10][11] , including the families in this current study 12 . Familial clustering of pancreas or other cancers may be influenced by shared environmental factors and by shared genes.…”
Section: Introductionmentioning
confidence: 85%
“…Although about 90% of pancreatic cancer patients report a negative family history of pancreatic cancer, familial clustering in the remaining 5% to 10% of the disease (presumably attributed to inheritance of moderate or high penetrance genes) has been reported (5)(6)(7)(8)(9). Formal case-control investigations provide persuasive evidence that a family history of pancreatic cancer is a risk factor, and some have further elaborated the role of cigarette smoking or age at diagnosis of pancreatic cancer in the family setting.…”
Section: Introductionmentioning
confidence: 99%
“…4 Enstrom found that the mor tality from pancreatic cancer among Mor mons in California and Utah was less than that for nonsmoking white males according to data obtained from the National Center for Health Statistics.5 Familial occurrence of pancreatic cancer is rare, but a few re ports have appeared; a familial tendency has not been well documented, however. 6 An apparent association between dia betes and pancreatic cancer has interested investigators for many years. While it is not unusual for diabetes to precede the diagnosis of pancreatic cancer by several months, there does not seem to be a causal relationship, at least in males.…”
Section: Epidemiologymentioning
confidence: 99%